PERKIRAAN WAKTU PEMBANGUNAN CANDI BERDASARKAN KESEGARISANNYA DENGAN MATAHARI - Nathanael Tantosa, Hardian
Archaeoastronomy is a field that studies the relation between ancient buildings and the sky, usually by seeing the alignment of an ancient building with a celestial object. In Indonesia, especially Java Island, there are a lot of temples from ancient civilization that can be researched. Several temples are researched in this Final Project, such as Borobudur Temple, Prambanan Temple, Kalasan Temple, and Mendut Temple. This Final Project will try to estimate the construction date of several temples in Java Island by matching the declination value of a temple with the Sun. The alignment of the temple with the Sun will also be checked. The declination value of a temple is obtained by transforming horizontal coordinates into equatorial coordinates. The Sun is chosen because of its declination value that changes greatly throughout the year, compared to other stars that have little change even throughout centuries. This Final Project also uses a software that is commonly used for archaeoastronomy research, such as Google Earth and thus have better precision than manual measurement.